Patofisiologi dan Tata Laksana Kardiotoksisitas yang Diinduksi Kemoterapi - Helen Widiani; Ida Bagus Rangga Wibhuti (PT Dexa Medica, 2026)
According to the European Society of Cardiology (ESC), cardiotoxicity is defined as damage of the function and/or structure of the heart associated with drug exposure, particularly anticancer therapies such as chemotherapy and radiotherapy,as well as damage caused by the cancer itself. Generally, chemotherapy-induced cardiotoxixity is classified into five types, with the two main types most frequently associated with high-risk antineoplastic therapy. Chemotherapy-inducedcardiotoxixity may occur through either direct or indirect mechanisms, with contributing factors including: accumulative dose, drug preparation, formulation, and drug delivery. The management of cardiotoxicity depends on the specific type ofcardiovascular disorder experienced by the patient. In cases of hypertension, angiotensin-converting enzyme inhibitors (ACEIs), or angiotensin receptor blockers (ARBs), along with dihydropyridine calcium channel blockers, are recommendedtherapeutic options. Anticancer therapy may be continued as long as the QT interval is ≤500 ms and the change in QT interval is <60 ms, and there is no evidence of ventricular arrhythmias or syncope. Management of atrial fibrillation is based on main considerations such as rhythm control and rate control, as well as thromboembolic prophylaxis. Prevention of cardiocicity begins with a comprehensive assessment of cardiovascular risk and predisposing factors. Patients with multiple risk factors, particularly when those are poorly controlled, and/or those with preexisting cardiovascular disease, should be managed as a high-risk patients.